Decoupling the Dynamics of Zinc Hydroxide Sulfate Precipitation/Dissolution in Aqueous Zn–MnO2 Batteries by Operando Optical Microscopy: A Missing Piece of the Mechanistic Puzzle. Issue 30 (13th June 2022) - Godeffroy, Louis; Aguilar, Ivette; Médard, Jérôme; Larcher, Dominique; Tarascon, Jean‐Marie; Kanoufi, Frédéric
Abstract: Energy storage provides flexibility to an energy system and is therefore key for the incorporation of renewable energy sources such as wind and solar into the grid. Aqueous Zn–MnO2 batteries are promising candidates for grid‐scale applications due to their high theoretical capacity (616 mAh g –1 ) and the abundance of their components in the Earth's crust. However, they suffer from low cyclability, which is probably linked to the dramatic pH variations induced by the electrochemical conversion of MnO2 . These pH variations are known to trigger the precipitation/dissolution of zinc hydroxide sulfate (Zn4 (OH)6 SO4  .  x H2 O, (ZHS)), which might have an influence on the conversion of MnO2 . Herein, optical reflectometry is used to image and quantitatively monitor the MnO2 electrode's charge and discharge in situ and under operation. It emphasizes how solid‐phase ZHS rules the dynamics of both charge and discharge, providing a comprehensive picture of the mechanism at play in aqueous Zn–MnO2 batteries. If the precipitation of ZHS might impede the MnO2 electrode's discharge, it is a crucial pH buffer delaying the occurrence of the competing oxidation of water on charge. Abstract : Imaging optical reflectometry is used to track operando the interrelated deposition/dissolution of MnO2 and zinc hydroxide sulfate in aqueous Zn–MnO2 batteries. Imaging and quantifying these processes reveal their implication in local pH variations and the two‐plateau charge–discharge profile.